Pengakuan Aset Tak Berwujud Dan Perbandingan Metode Garis Lurus Dengan Metode Saldo Menurun Dalam Menentukan Pajak Penghasilan - Puji Rahayu; Hariana Septian (LPPM ISNJ Bengkalis, 2020)
The purpose of this study is to analyze the recognition of intangible assets and to compare the straights line method with the declining balance method in determining income tax. The method in this research is evaluation and qualitative research type. From the results of the research, it was identified that the company has intangible assets in the form of a personnel information system worth IDR 35,000,000, all costs used to obtain the system are recognized as intangible assets according to the criteria for intangible assets according to PSAK 19. Amortization calculation results in 2019 using the straight-line method amounted to IDR 8,750,000. So that the commercial comprehensive income generated is IDR 27,425,574,392. Meanwhile, the declining balance method resulted in amortization of IDR 17,500,000 and the resulting comprehensive commercial profit of IDR 27,416,824,392. After the fiscal reconciliation was carried out, the Income Tax amounted to IDR 6,285,027,465 using a straight line as the amortization calculation. Meanwhile, Income Tax with amortization costs uses the declining balance method of IDR 6,282,964,965. There is a tax savings of IDR 2,062,500 if you use the Decreasing Balance Method. So that the declining balance method is very suitable to use when economic conditions are sluggish like today due to the impact of Covid-19. The tax savings can be used to increase the company's capital to run business operations.